Narasi Ketimpangan Sosial dalam Pertunjukan Topeng Banjet Abah Pendul Lakon Cerita Gordon Muda - Rudi Hartono; Arthur S. Nalan; Yanti Heriyawati (Pascasarjana ISBI Bandung, 2022)
Mask Banjet is a folk theater which was born and developed from the community in Karawang Regency. The focus of this study is on the play of Topeng Banjet Abah Pendul performance. The analysis applies a critical sociology of art approach. In this study, the text of the play story which has been analyzed as a source of document data is Gordon Muda as a representation of the story text. Social inequality narratives are found to be thematic. The story of the play is presented in a comedic way with the story of Odah as a wife whose husband is left helpless economically. Her child is hungry. Buying rice is very difficult. To fulfil the necessities of life, various affairs are carried out such as being washermen, farm laborers, lawn mowers, selling fried food and borrowing money from Emok Bank. Gordon Young and his men carried out robberies. The robberies were planned to be used as the business capital. The description in the story above is the narrative of social inequality in the text of the performance. The text for the description of the story shows the conditions of the existing social factsKeywords: Performance play, Social Inequality, Sociology of the Arts